IgA nephropathy: a review of existing and emerging therapies - Noor, Sahibzadi Mahrukh; Abuazzam, Farah; Mathew, Roy; Zhang, Zhiwei; Abdipour, Amir; Norouzi, Sayna (Frontiers in Nephrology, 2023)
IgA nephropathy is the most common primary glomerulonephritis worldwide. Recently, there have been multiple advances in the understanding of IgA nephropathy pathophysiology and therapeutic options. Despite the advent of new treatment options, individual risk stratification of the disease course and choosing the best treatment strategy for the patient remains challenging. A multitude of clinical trials are ongoing, opening multiple opportunities for enrollment. In this brief review, we discuss the current approach to the management of IgA nephropathy and highlight the ongoing clinical trials.